2016
DOI: 10.21829/myb.2016.2221326
|View full text |Cite
|
Sign up to set email alerts
|

Germinación y emergencia de plántulas de cuatro especies de encino amenazadas

Abstract: Germination and emergence of the endangered cloud forest oak species Quercus germana, Q. insignis, Q. sartorii and Q. xalapensis were observed under different light conditions (sun vs. shade) in a secondary forest fragment (SFF) and in a greenhouse (GRE). Seed weight variability was evaluated for each species and its relationship to germination and emergence determined. After 60 days, a total of 62.17% of the acorns had germinated and 37.79% had emerged in both experiments. Germination was highest in Q. sartor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
(30 reference statements)
1
1
0
Order By: Relevance
“…Although the data for sweet chestnut is limited, the connection between seed size, germination rate and survival has been well-studied in another Fagaceae genus, i.e., oak (Quercus L.). Our results are in accordance with Alptekin and Tilki [38] and Garcia-De La Cruz et al [39], who concluded that seed size did not affect the acorn germination rate or seedling emergence of the four analyzed oak species. On the other hand, Purohit et al [40] and Pandey et al [41] described a positive relationship between seed size and germination rate in oaks.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Although the data for sweet chestnut is limited, the connection between seed size, germination rate and survival has been well-studied in another Fagaceae genus, i.e., oak (Quercus L.). Our results are in accordance with Alptekin and Tilki [38] and Garcia-De La Cruz et al [39], who concluded that seed size did not affect the acorn germination rate or seedling emergence of the four analyzed oak species. On the other hand, Purohit et al [40] and Pandey et al [41] described a positive relationship between seed size and germination rate in oaks.…”
Section: Resultssupporting
confidence: 93%
“…Similar positive correlations between seed mass and germination rate were documented in other plant species [42][43][44][45][46]. These different results, even within the same genus, can possibly be explained as a species-specific reaction to the environmental conditions, variation in maternal origin, differences in provenance and intraspecific variation within a larger range of a species [39,47]. However, storage and proper stratification prior to sowing can also influence the germination and subsequent development of seedlings [32].…”
Section: Resultsmentioning
confidence: 57%